2008
DOI: 10.1016/j.bbagrm.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mammalian microRNA processing and function by cellular signaling and subcellular localization

Abstract: For many microRNAs, in many normal tissues and in cancer cells, the cellular levels of mature microRNAs are not simply determined by transcription of microRNA genes. This mini-review will discuss how microRNA biogenesis and function can be regulated by various nuclear and cytoplasmic processing events, including emerging evidence that microRNA pathway components can be selectively regulated by control of their subcellular localization and by modifications that occur during dynamic cellular signaling. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Similarly, dicer and RISC components are locally expressed in close proximity to the pre-miRs, and appear to comprise a system for local activity-dependent formation of mature miRNAs and local regulation of protein translation. This is consistent with precedents in various cell types showing that specific pre-miRs can be expressed yet inhibited from further processing into mature miRNAs (reviewed in Smalheiser 2008a). As well, several stable primary miRNA gene transcripts (pri-miRs) have been shown to be expressed in the cytoplasm (e.g., BIC; Eis et al 2005) and one pri-miR has been shown to be localized sub-synaptically at the rat neuromuscular junction (Velleca et al 1994).…”
Section: Introductionsupporting
confidence: 91%
“…Similarly, dicer and RISC components are locally expressed in close proximity to the pre-miRs, and appear to comprise a system for local activity-dependent formation of mature miRNAs and local regulation of protein translation. This is consistent with precedents in various cell types showing that specific pre-miRs can be expressed yet inhibited from further processing into mature miRNAs (reviewed in Smalheiser 2008a). As well, several stable primary miRNA gene transcripts (pri-miRs) have been shown to be expressed in the cytoplasm (e.g., BIC; Eis et al 2005) and one pri-miR has been shown to be localized sub-synaptically at the rat neuromuscular junction (Velleca et al 1994).…”
Section: Introductionsupporting
confidence: 91%
“…The differences in targeting characteristics between miRNAs may be due to individual miRNAs existing in differing cell compartments. Some miRNAs are spatially trafficked specifically to particular parts of the cell (nucleus versus cytoplasm, and dendrites versus axons, for example) and these compartmental differences might be accompanied by differing target determinants 3236. Alternatively, particular miRNAs may interact selectively with different proteins—miRNAs comprise only a small portion of miRNPs and AGO is only one of the many miRNP-associated proteins 7,8,21,37.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression regulation by miRNA is at least partially due to binding the 3 0 -untranslated region (3 0 UTR) of target mRNA, which contributes to repressing protein translation. In many cases, bound miRNA also decreases the stability of target mRNA resulting in RNA transcript degradation [9,10]. In addition to their role in normal biological processes, miRNAs are involved in various diseases, including MM [10][11][12].…”
Section: Introductionmentioning
confidence: 99%